초소형 고감도 나노 바이오 센서의 연구개발 및 시장 동향 - 박형식; 국준원; 최권영; 이재현 (전기전자재료학회논문지, 2023)
This paper presents the development and market trends of nano biosensors. These biosensors must possess high sensitivity and selectivity to effectively detect diseases. Presently, many research groups are focusing on the field-effect transistor aspect of nano biosensors, which can identify diseases such as Down syndrome, bladder cancer, breast cancer, and numerous other cancers, utilizing graphene and transition metal dichalcogenide materials. In the case of in-vitro diagnostics, the use of nano biosensors has been rapidly growing since the onset of the COVID-19 pandemic. This paper also discusses market trends and the outlook for both national and international enterprises engaged in the nano biosensor field. Nano biosensors are expected to play a beneficial and significant role soon, contributing to the early diagnosis of diseases and subsequently improving patient outcomes.
Keywords: Biosensor; FET; Nanoparticle; Sensitivity; Selectivity